A hardening film and preparation method thereof

By using magnetron sputtering layer and photocuring composition in the in-mold transfer hardened film, the problem of difficult peeling of the hardened layer and the release layer is solved, the product yield and adhesion are improved, and the process flow is simplified.

CN116410509BActive Publication Date: 2025-02-18NINGBO ANTFOR NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210079860.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-12-29
Filing Date
2022-01-24
Publication Date
2025-02-18
Estimated Expiration
2042-01-24

AI Technical Summary

Technical Problem

The hardened layer of the existing hardened film for in-mold transfer is difficult to peel off from the release layer, which affects product yield, and the heating process will lead to silicon migration, reducing the release force and the performance of the hardened layer.

Method used

A magnetron sputtering layer is used to replace the traditional release layer, and a photocuring composition and additives are added to the hardened layer to form a hardened film structure that is easy to peel.

Benefits of technology

The peeling force between the hardened layer and the release layer is improved, the product yield is improved, the silicon migration problem is avoided, the adhesion between the hardened layer and the ink layer is enhanced, and the production efficiency is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116410509B_ABST
    Figure CN116410509B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of in-mold transfer technology (IMR), and specifically to a hardened film for IMR and a preparation method thereof. In order to solve the problem that the hardened layer of the existing hardened film for in-mold transfer is difficult to peel off from the substrate, the present invention provides a hardened film for in-mold transfer and a preparation method thereof. The hardened film comprises a substrate, a magnetron sputtering layer and a hardened layer in sequence. The hardened layer of the hardened film for in-mold transfer is easy to peel off from the magnetron sputtering layer, which greatly improves the yield of the product. Compared with the traditional process, there is one less ink adhesion enhancement layer, which improves the production efficiency of the hardened film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of in-mold transfer (IMR) technology, and in particular to a hardening film for IMR and a preparation method thereof. Background Art

[0002] With the continuous development of surface treatment processes such as electroplating, painting, real wood, thermal transfer, digital printing, electrophoresis, skinning, and water transfer, people are paying more and more attention to the design of industrial product appearance, such as fashion, environmental protection, and lightweight design. This makes the in-mold transfer technology (IMR: In-Mold by Roller-Film) that can be integrated into injection molding more and more popular. IMR technology is to print the pattern on the film, then place the film on the dynamic mold wall, and then inject the plastic into the ink layer on the back of the film, and finally tear off the film, so that the pattern on the film is transferred to the surface of the plastic product. This is a technology that realizes the integrated molding of decorative patterns and plastic substrates.

[0003] The existing manufacturing process of hardened film for in-mold transfer is complicated, such as Figure 1 As shown, the hardened film is generally composed of a base film 01, a release layer 02, a hardened layer 03, and an ink adhesion enhancing layer 04. Both the release layer and the hardened layer are cured by thermal reaction, which is a time-consuming and labor-intensive process. The latter stage requires ink printing, metal evaporation and other processes, including multiple heating processes. Heating will increase the peeling force between the release layer and the hardened layer. The increased peeling force will cause the hardened layer and the release layer to be unable to be separated or part of the hardened layer will remain on the release layer during peeling, causing the product to be scrapped. The latter stage of IMR will seriously affect (seriously affecting the release layer, which is generally a layer of silicone oil applied on the base film. Multiple heating will cause silicon to migrate to the hardened layer, reducing the silicon content of the release layer and increasing the release force. At the same time, silicon transfer will cause the hardened layer surface to turn white and its wear resistance to deteriorate) the peeling of the hardened layer and the release layer, ultimately affecting the yield of the entire IMR film. Summary of the invention

[0004] In order to solve the problem that the hardening layer and the release layer of the existing hardening film for in-mold transfer are difficult to peel off, the present invention provides a hardening film for in-mold transfer and a preparation method thereof. The hardening layer of the hardening film for in-mold transfer is easy to peel off from the magnetron sputtering layer, which greatly improves the yield of the product. Compared with the traditional process, there is one less ink adhesion enhancement layer, which improves the production efficiency of the hardening film.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions.

[0006] The present invention provides a hardened film, which comprises a substrate, a magnetron sputtering layer and a hardened layer in sequence.

[0007] Furthermore, the magnetron sputtering layer is a silicon nitride layer or a silicon oxide layer.

[0008] The present invention provides a hardened film, which comprises a substrate, a silicon nitride layer and a hardened layer in sequence.

[0009] The present invention uses a magnetron sputtering layer to replace the traditional release layer. The magnetron sputtering layer does not increase the adhesion with the hardened layer due to the heating process, thereby enhancing the stability of the peeling force between the substrate and the hardened layer. At the same time, the hardened layer will not have silicon transfer, thereby ensuring the quality of the hardened film product.

[0010] Furthermore, the hardened layer is formed from a photocurable composition.

[0011] Further, the photocurable composition comprises 24-35 parts by weight of tetrafunctional polyurethane acrylate oligomer, 28-38 parts by weight of trimethylolpropane triacrylate, 7-10 parts by weight of acrylic polyol, 2-4 parts by weight of isocyanate, 0.3-0.7 parts by weight of photoinitiator, 0.1-0.4 parts by weight of leveling agent, 0.2-0.4 parts by weight of nano-silicon dioxide particles, and 24-25 parts by weight of solvent butanone. The total parts of the tetrafunctional polyurethane acrylate oligomer, trimethylolpropane triacrylate, acrylic polyol, isocyanate, photoinitiator, leveling agent, nano-silicon dioxide particles, and solvent are 100 parts by weight.

[0012] The main resin is tetrafunctional polyurethane acrylate oligomer. Trimethylolpropane triacrylate is the surface diluent. Acrylic polyol and isocyanate are ink adhesion enhancers, which are used to improve the adhesion between the hardening layer and the ink layer. Nano-silicon dioxide can enhance the hardness of the coating.

[0013] Furthermore, the magnetron sputtering layer is a silicon nitride layer.

[0014] Furthermore, the thickness of the magnetron sputtering layer is 30-70 nm.

[0015] Furthermore, the thickness of the hardened layer is 4-8 μm.

[0016] Furthermore, the thickness of the substrate is 75-188 μm.

[0017] Further, the photocurable composition includes 28-30 parts by weight of tetrafunctional aliphatic polyurethane acrylate oligomer, 30-32 parts by weight of trimethylolpropane triacrylate, 10 parts by weight of acrylic polyol, 4 parts by weight of isocyanate, 0.5-0.6 parts by weight of photoinitiator, 0.1-0.2 parts by weight of leveling agent, 0.2-0.4 parts by weight of nano-silicon dioxide particles, and 25 parts by weight of solvent butanone. The total number of parts of the tetrafunctional polyurethane acrylate oligomer, trimethylolpropane triacrylate, acrylic polyol, isocyanate, photoinitiator, leveling agent, nano-silicon dioxide particles, and solvent is 100 parts by weight. The above technical solution includes Example 1 and Example 4.

[0018] Further, the photocurable composition includes 30 parts by weight of tetrafunctional aliphatic polyurethane acrylate oligomer, 30 parts by weight of trimethylolpropane triacrylate, 10 parts by weight of acrylic polyol, 4 parts by weight of isocyanate, 0.5 parts by weight of photoinitiator, 0.1 parts by weight of leveling agent, 0.4 parts by weight of nano-silica particles, and 25 parts by weight of solvent butanone. The above technical solution includes embodiment 1.

[0019] The present invention provides a method for preparing a hardened film, the method comprising the following steps:

[0020] Step 1, magnetron sputtering a layer of silicon nitride coating on the substrate;

[0021] Step 2: prepare a photocurable composition, apply the photocurable composition onto the magnetron sputtering layer, and dry and cure the coating to obtain a hardened layer.

[0022] Furthermore, the preparation method of the hardened film for in-mold transfer provided by the present invention comprises the following steps: step one, magnetron sputtering a layer of silicon nitride coating on the substrate; step two, preparing a photocurable composition, applying the photocurable composition onto the magnetron sputtering layer, drying the formed coating at 80-90°C for 4 minutes, and then curing the dried coating by ultraviolet rays from a high-pressure mercury lamp to obtain a hardened layer.

[0023] Compared with the prior art, the present invention has the following advantages:

[0024] 1. The present invention simplifies the structure of the hardened film for IMR, which consists of a thin film layer (substrate layer, referred to as substrate), a magnetron sputtering layer and a hardened layer, does not contain an ink adhesion enhancement layer, reduces the film manufacturing process, and improves production efficiency;

[0025] 2. The present invention utilizes the easy peeling characteristic between the magnetron sputtering layer and the hardened layer, and the peeling force between the magnetron sputtering layer and the hardened layer is not affected by the heating process, which can improve the yield of the IMR product. At the same time, an additive for improving the adhesion of the ink is added to the hardened layer (the additive refers to acrylic polyol and isocyanate. Acrylic polyol reacts with isocyanate and contains isocyanate groups at the end, which can react with hydroxyl groups in the ink to increase the adhesion of the ink) to enhance the adhesion between the hardened layer and the ink layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a structural schematic diagram of an existing hardening film;

[0027] Figure 2 This is a schematic structural diagram of the hardening film provided by the present invention. DETAILED DESCRIPTION

[0028] The present invention is described in detail below with reference to specific embodiments and drawings, but the present invention is not limited thereto.

[0029] like Figure 2 As shown, the hardened film provided by the present invention includes a base film (also called a substrate) 1, a magnetron sputtering layer 2 and a hardened layer 3.

[0030] The performance of the hardened film provided by the present invention is tested according to the following method:

[0031] (1) Pencil hardness

[0032] Use Elcometer 3086 pencil hardness tester to measure the pencil hardness of the sample. Measurement method: Use Mitsubishi pencil with hardness of H~9H to draw 5 lines under 500g load, then observe whether the hardened coating is scratched and judge according to the following standards.

[0033] Criteria

[0034] 0 to 1 scratch, judged as "Pass";

[0035] If there are 2 to 5 scratches, it will be judged as "NG" (failed).

[0036] (2) Wear resistance

[0037] Use Kunshan Jingjia Instrument A20-339 steel wool resistance tester at 500gf / cm 2 Under a load of 1 kg, use #0000 steel wool to rub back and forth on the surface of the hardened layer 1000 times to check whether the coating is scratched.

[0038] Criteria:

[0039] If there are 0 scratches, the test result is “Pass”.

[0040] If there is ≥1 scratch, it will be judged as “NG” (failed).

[0041] (3) Interlayer adhesion / peeling force between hardened layer and magnetron sputtered layer

[0042] The tape was laminated to the hardened layer and placed at room temperature for 30 minutes. Then, a HD-B609B-S tensile testing machine from Haida Instruments was used to perform a peel test at an angle of 180° and a speed of 300 mm / min. The peel force between the hardened layer and the magnetron sputtered layer was recorded.

[0043] (3) Hardened layer peeling integrity

[0044] Lay the tape on the hardened layer and place it at room temperature for 30 minutes. Then use the HD-B609B-S tensile testing machine of Haida International Instruments to peel the hardened layer from the magnetron sputtering layer and observe whether there is any hardened film left on the magnetron sputtering layer or whether the hardened layer on the tape is cracked.

[0045] No residue and no cracking, judged as "Pass";

[0046] If there is residue or cracking, it will be judged as "NG" (unqualified).

[0047] (4) Ink adhesion

[0048] Apply the ink on the hardening layer. After it is completely cured, use the 100-grid method to measure. Use a 100-grid knife to draw 11 horizontal and vertical cross lines on the ink layer to form 100 squares of 1 cm in size. Use 3M Cotch 600 tape to test. If the printed ink layer does not fall off, it is marked as 100. If it falls off, the remaining amount is marked as that. For example, if there are only 5 squares left in the printed ink layer that have not fallen off, it is marked as 5.

[0049] Example 1

[0050] The invention provides a hardened film and a preparation method thereof. The hardened film comprises a substrate, a magnetron sputtering layer and a hardened layer.

[0051] Silicon nitride was sputtered onto one surface of an optical grade polyethylene terephthalate film (manufactured by a Korean company, trade name: XG7PL2) with a thickness of 188 microns by magnetron sputtering to obtain a magnetron sputtering layer. The thickness of the magnetron sputtering layer was 50 nm.

[0052] 30 parts by weight of tetrafunctional aliphatic polyurethane acrylate oligomer, 30 parts by weight of trimethylolpropane triacrylate, 10 parts by weight of acrylic polyol, 4 parts by weight of isocyanate, 0.5 parts of photoinitiator 184, 0.1 parts by weight of leveling agent BYK-333, 0.4 parts of nano-silica particles, and 25 parts by weight of solvent butanone are mixed to obtain a photocurable composition.

[0053] The photocurable composition was applied to the surface of the magnetron sputtering layer. After the formed coating was dried at 80-90°C for 4 minutes, the photocurable composition was coated with 500 mJ / cm 2 The dried coating was cured by ultraviolet irradiation with a light intensity of 100 μm to obtain a hardened layer. The thickness of the hardened layer was 6 μm.

[0054] Example 2

[0055] The photocurable composition and cured film provided in Example 1.

[0056] Silicon oxide was sputtered onto one surface of a 100 μm thick optical grade polyethylene terephthalate film (manufactured by a Korean company, trade name: XG7PL2) by magnetron sputtering to obtain a magnetron sputtering layer. The thickness of the magnetron sputtering layer was 30 nm.

[0057] 35 parts by weight of tetrafunctional aliphatic polyurethane acrylate oligomer, 28 parts by weight of trimethylolpropane triacrylate, 9 parts by weight of acrylic polyol, 3 parts by weight of isocyanate, 0.3 parts of photoinitiator 184, 0.4 parts by weight of leveling agent BYK-333, 0.3 parts of nano-silica particles, and 24 parts by weight of solvent butanone are mixed to obtain a photocurable composition.

[0058] The above-mentioned photocurable composition was applied to the surface of the magnetron sputtering layer. After the formed coating was dried at 80-90°C for 4 minutes, the photocurable composition was coated with 500 mJ / cm 2 The dried coating was cured by ultraviolet irradiation with a light intensity of 100 μm to obtain a hardened layer. The thickness of the hardened layer was 4 μm.

[0059] Example 3

[0060] The photocurable composition and cured film provided in Example 1.

[0061] Silicon nitride was sputtered onto one surface of a 75 micron thick optical grade polyethylene terephthalate film (manufactured by a Korean company, trade name: XG7LN8) by magnetron sputtering to obtain a magnetron sputtering layer. The thickness of the magnetron sputtering layer was 70 nm.

[0062] 24 parts by weight of tetrafunctional aliphatic polyurethane acrylate oligomer, 38 parts by weight of multifunctional active monomer trimethylolpropane triacrylate, 8 parts by weight of acrylic polyol, 4 parts by weight of isocyanate, 0.7 parts of photoinitiator 184, 0.1 parts by weight of leveling agent BYK-333, 0.2 parts of nano-silica particles, and 25 parts by weight of solvent butanone are mixed to obtain a photocurable composition.

[0063] The photocurable composition was coated on the surface of the magnetron sputtering layer. After the formed coating was dried at 80-90°C for 4 minutes, the photocurable composition was coated at 500 mJ / cm 2 The dried coating was cured by ultraviolet irradiation with a light intensity of 100 μm to obtain a hardened layer. The thickness of the hardened layer was 8 μm.

[0064] Example 4

[0065] The photocurable composition and cured film provided in Example 1.

[0066] Silicon oxide was sputtered onto one surface of a 100 μm thick optical grade polyethylene terephthalate film (manufactured by a Korean company, trade name: XG7PL2) by magnetron sputtering to obtain a magnetron sputtering layer. The thickness of the magnetron sputtering layer was 40 nm.

[0067] 28 parts by weight of tetrafunctional aliphatic polyurethane acrylate oligomer, 32 parts by weight of trimethylolpropane triacrylate, 10 parts by weight of acrylic polyol, 4 parts by weight of isocyanate, 0.6 parts of photoinitiator 184, 0.2 parts by weight of leveling agent BYK-333, 0.2 parts of nano-silica particles, and 25 parts by weight of solvent butanone are mixed to obtain a photocurable composition.

[0068] The photocurable composition was coated on the surface of the magnetron sputtering layer. After the formed coating was dried at 80-90°C for 4 minutes, the photocurable composition was coated at 500 mJ / cm 2 The dried coating was cured by ultraviolet irradiation with a light intensity of 100 μm to obtain a hardened layer. The thickness of the hardened layer was 7 μm.

[0069] Example 5

[0070] The photocurable composition and cured film provided in Example 1.

[0071] Silicon nitride was sputtered onto one surface of a 75 micron thick optical grade polyethylene terephthalate film (manufactured by a Korean company, trade name: XG7LN8) by magnetron sputtering to obtain a magnetron sputtering layer. The thickness of the magnetron sputtering layer was 60 nm.

[0072] 35 parts by weight of tetrafunctional aliphatic polyurethane acrylate oligomer, 30 parts by weight of multifunctional active monomer trimethylolpropane triacrylate, 7 parts by weight of acrylic polyol, 2 parts by weight of isocyanate, 0.4 parts of photoinitiator 184, 0.3 parts by weight of leveling agent BYK-333, 0.3 parts of nano-silica particles, and 25 parts by weight of solvent butanone are mixed to obtain a photocurable composition.

[0073] The photocurable composition was coated on the surface of the magnetron sputtering layer. After the formed coating was dried at 80-90°C for 4 minutes, the photocurable composition was coated at 500 mJ / cm 2 The dried coating was cured by ultraviolet irradiation with a light intensity of 5 μm to obtain a hardened layer. The thickness of the hardened layer was 5 μm.

[0074] Comparative Example 1

[0075] Silicon nitride was sputtered onto one surface of a 100 μm thick optical grade polyethylene terephthalate film (manufactured by a Korean company, trade name: XG7PL2) by magnetron sputtering to obtain a magnetron sputtering layer. The thickness of the magnetron sputtering layer was 60 nm.

[0076] 35 parts by weight of tetrafunctional aliphatic polyurethane acrylate oligomer, 40 parts by weight of trifunctional active monomer trimethylolpropane triacrylate, 0.5 parts of photoinitiator 184, 0.2 parts by weight of leveling agent BYK-333, 0.3 parts of nano-silica particles, and 24 parts by weight of solvent butanone are mixed to obtain a photocurable composition.

[0077] The photocurable composition was coated on the surface of the magnetron sputtering layer. After the formed coating was dried at 80-90°C for 4 minutes, the photocurable composition was coated at 500 mJ / cm 2 The dried coating was cured by ultraviolet irradiation with a light intensity of 100 μm to obtain a hardened layer. The hardened layer thickness was 6 μm.

[0078] Compared with the technical solution provided by the present invention, the difference in Comparative Example 1 is that no acrylic polyol and isocyanate are added to the formulation of the photocurable composition.

[0079] Comparative Example 2

[0080] A release layer is coated on one surface of an optical grade polyethylene terephthalate film (manufactured by a Korean company, trade name: XG7PL2) with a thickness of 188 μm. The thickness of the release layer is 1 μm.

[0081] 25 parts by weight of tetrafunctional aliphatic polyurethane acrylate oligomer, 35 parts by weight of trifunctional active monomer trimethylolpropane triacrylate, 10 parts by weight of acrylic polyol, 5 parts by weight of isocyanate, 0.6 parts of photoinitiator 184, 0.1 parts by weight of leveling agent BYK-333, 0.3 parts of nano-silica particles, and 24 parts by weight of solvent butanone are mixed to obtain a photocurable composition.

[0082] The above-mentioned photocurable composition was applied to the release surface. After the formed coating was dried at 80-90°C for 4 minutes, the photocurable composition was heated at 500 mJ / cm 2The dried coating was cured by ultraviolet irradiation with a light intensity of 100 μm to obtain a hardened layer. The thickness of the hardened layer was 7 μm.

[0083] Compared with the technical solution provided by the present invention, the difference of Comparative Example 2 is that the IMR diaphragm structure is replaced by a release layer instead of a magnetron sputtering layer.

[0084] Table 1 Performance test results of the hardened films provided by Examples 1-5 and Comparative Examples 1-2

[0085]

[0086] The hardened film for IMR provided by the present invention has good comprehensive performance, and has the properties of high hardness, high wear resistance, easy interlayer peeling, good ink adhesion, etc. Among them, the hardened films provided by Example 1 and Example 4 have better comprehensive performance: high hardness, low interlayer peeling force, qualified wear resistance, qualified hardened layer peeling integrity, and high ink adhesion. In particular, the hardened film provided by Example 1 has the best comprehensive performance.

[0087] It should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. All equivalent changes and modifications made according to the content of the present invention are included in the patent scope of the present invention.

Claims

1. A hardened film for IMR, characterized in that: The hardened film is composed of a substrate, a magnetron sputtering layer and a hardened layer in sequence; the magnetron sputtering layer is a silicon nitride layer or a silicon oxide layer; the hardened layer is formed by a photocurable composition; The photocurable composition comprises 24-35 parts by weight of a tetrafunctional polyurethane acrylate oligomer, 28-38 parts by weight of trimethylolpropane triacrylate, 7-10 parts by weight of acrylic polyol, 2-4 parts by weight of isocyanate, 0.3-0.7 parts by weight of a photoinitiator, 0.1-0.4 parts by weight of a leveling agent, 0.2-0.4 parts by weight of nano-silicon dioxide particles, and 24-25 parts by weight of a solvent, butanone; the total parts of the tetrafunctional polyurethane acrylate oligomer, trimethylolpropane triacrylate, acrylic polyol, isocyanate, photoinitiator, leveling agent, nano-silicon dioxide particles, and solvent are 100 parts by weight.

2. The cured film for IMR according to claim 1, wherein: The thickness of the magnetron sputtering layer is 30-70 nm.

3. The cured film for IMR according to claim 1, wherein: The thickness of the hardened layer is 4-8μm.

4. The cured film for IMR according to claim 1, wherein: The thickness of the substrate is 75-188 μm.

5. The hardened film for IMR according to claim 1, wherein: The photocurable composition comprises 28-30 parts by weight of a tetrafunctional aliphatic polyurethane acrylate oligomer, 30-32 parts by weight of trimethylolpropane triacrylate, 10 parts by weight of acrylic polyol, 4 parts by weight of isocyanate, 0.5-0.6 parts by weight of a photoinitiator, 0.1-0.2 parts by weight of a leveling agent, 0.2-0.4 parts by weight of nano-silicon dioxide particles, and 25 parts by weight of a solvent, butanone; the total parts of the tetrafunctional polyurethane acrylate oligomer, trimethylolpropane triacrylate, acrylic polyol, isocyanate, photoinitiator, leveling agent, nano-silicon dioxide particles, and solvent are 100 parts by weight.

6. A method for preparing a hardened film for IMR according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: Step 1: magnetron sputtering a magnetron sputtering layer on the substrate; Step 2: Prepare a photocurable composition, apply the photocurable composition onto the magnetron sputtering layer, and dry and cure the coating to obtain a hardened layer.

Citation Information

Patent Citations

  • Hard coating film with high dyne value

    CN106634462A

  • Printable double-sided hard coated film

    CN106750459A

  • Barrier film and preparation method thereof

    CN107293627A